2003
DOI: 10.4049/jimmunol.171.7.3863
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin (Diferuloylmethane) Inhibits Constitutive and IL-6-Inducible STAT3 Phosphorylation in Human Multiple Myeloma Cells

Abstract: Numerous reports suggest that IL-6 promotes survival and proliferation of multiple myeloma (MM) cells through the phosphorylation of a cell signaling protein, STAT3. Thus, agents that suppress STAT3 phosphorylation have potential for the treatment of MM. In the present report, we demonstrate that curcumin (diferuloylmethane), a pharmacologically safe agent in humans, inhibited IL-6–induced STAT3 phosphorylation and consequent STAT3 nuclear translocation. Curcumin had no effect on STAT5 phosphorylation, but inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
310
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(326 citation statements)
references
References 72 publications
14
310
0
2
Order By: Relevance
“…Besides its effect on STAT proteins in leukemia cells, curcumin was also reported to be a reversible inhibitor of constitutive STAT3, but not STAT5 phosphorylation, in human MM cells (Bharti et al 2003). This was correlated with the inhibition of STAT3 nuclear translocation in MM cells.…”
Section: Multiple Myelomamentioning
confidence: 94%
“…Besides its effect on STAT proteins in leukemia cells, curcumin was also reported to be a reversible inhibitor of constitutive STAT3, but not STAT5 phosphorylation, in human MM cells (Bharti et al 2003). This was correlated with the inhibition of STAT3 nuclear translocation in MM cells.…”
Section: Multiple Myelomamentioning
confidence: 94%
“…Recently, two studies revealed the expression of constitutively active NF-kB in freshly drawn bone marrow aspirates from 37 of 37 MM patients. 40,41 Both studies demonstrated the retention of the NF-kB consensus sequence in nuclear extracts as well as translocation of the p65 subunit to the nucleus in highly purified CD138 þ MM plasma cells. The underlying mechanisms for expression of constitutively activated NF-kB in MM cells are poorly understood.…”
Section: Non-hodgkin's Lymphomamentioning
confidence: 96%
“…42 As a possibility, NF-kB might upregulate the expression of interleukin-6 (IL-6), which in turn activates STAT3. 40,41 The expression of Bcl-X L , a prominent antiapoptotic Bcl-2 homolog, is induced by both STAT3 and NF-kB, and Bcl-X L overexpression has been demonstrated in MM cells at the protein level. 42 The expression of Bcl-X L is negatively correlated with chemotherapy responses in MM.…”
Section: Non-hodgkin's Lymphomamentioning
confidence: 99%
“…In studies of the myeloid cell line ML-1a, Singh and Aggarwal reported that curcumin inhibited IkBa phosphorylation, degradation, and NF-kB translocation induced by a diverse range of stimuli including TNF, hydrogen peroxide, and phorbol esters [2]. Subsequent studies confirmed curcumininduced inhibition of NF-kB translocation in multiple cell types, including colon [3], gastric [4], pancreatic [5], and squamous epithelial tumor cell lines [6] as well as B-cell lymphoma and multiple myeloma cell lines [7,8]. Although the precise mechanism by which NF-kB translocation is inhibited remains unclear, Plummer et al demonstrated that curcumin reduced NF-kB translocation in HEK293 cells transfected with NIK, IKKa, or IKKb kinases [3].…”
Section: Introductionmentioning
confidence: 91%